(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Urinary tract infections (UTIs) remain the common infections diagnosed in outpatients as well as hospitalized patients. Multi-drug resistance (MDR) and extensively-drug resistance (XDR) in bacteria is an alarming problem in the world. The aim of this study was to detection of etiologic agents associated with community-acquired urinary tract infections (CA-UTIs) and investigation of antibiotic susceptibility patterns.Methods: This study was performed from September 2014 to March 2015 on outpatients, which referred to Labbafinejad Hospital Clinic, Tehran, Iran. The bacterial pathogenic diversity identified by standard laboratory methods. The antimicrobial resistance rates were performed by Kirby Bauer disc diffusion methods.Results: A total of 303 patients were enrolled in this study, from which 204 (67.3%) were female and 99 (32.5%) were male patients. Escherichia coli was the dominant species (69%), followed by Enterococcus faecalis (12.8%) and Klebsiella pneumoniae (4.6%). High resistance rate to nalidixic acid (73.8%), trimethoprim/Sulfamethoxazole (54.3%), ciprofloxacin (54.3%) in E. coli, and tetracycline (89.7%) in E. faecalis strains and high susceptibility rate to meropenem (96.6%), imipenem (95.2%), amikacin (90.4%), cefoxtin (87.6%), and nitrofurantoin (82.8%) in E. coli, and nitrofurantoin (100%) in E. faecalis strains were observed. In addition, 43.5% of the strains were multidrug-resistant (MDR).Conclusions: This study showed that E. coli was the predominant uropathogen of CA-UTIs in this geographical area. It also demonstrated the empirical treatment of urinary tract infections may be difficult due to high resistance to commonly used antibiotics. Continuous monitoring of MDR organisms and drug resistance patterns are needed to prevent treatment failure and reduce selective pressure. These findings suggest the use of nitrofurantoin, cefoxitin, and amikacin in this area of the country.